Humanized Mice Exhibit Exacerbated Abscess Formation and Osteolysis During the Establishment of Implant-Associated Staphylococcus aureus Osteomyelitis - Muthukrishnan, Gowrishankar; Wallimann, Alexandra; Rangel-Moreno, Javier; Bentley, Karen L. de Mesy; Hildebrand, Maria; Mys, Karen; Kenney, H. Mark; Sumrall, Eric T.; Daiss, John L.; Zeiter, Stephan; Richards, R. Geoff; Schwarz, Edward M.; et al. (Frontiers in Immunology, 2021)
Staphylococcus aureus is the predominant pathogen causing osteomyelitis. Unfortunately, no immunotherapy exists to treat these very challenging and costly infections despite decades of research, and numerous vaccine failures in clinical trials. This lack of success can partially be attributed to an overreliance on murine models where the immune correlates of protection often diverge from that of humans. Moreover, S. aureus secretes numerous immunotoxins with unique tropism to human leukocytes, which compromises the targeting of immune cells in murine models. To study the response of human immune cells during chronic S. aureus bone infections, we engrafted non-obese diabetic (NOD)–scid IL2Rγnull (NSG) mice with human hematopoietic stem cells (huNSG) and analyzed protection in an established model of implant-associated osteomyelitis. The results showed that huNSG mice have increases in weight loss, osteolysis, bacterial dissemination to internal organs, and numbers of Staphylococcal abscess communities (SACs), during the establishment of implant-associated MRSA osteomyelitis compared to NSG controls (p <0.05). Flow cytometry and immunohistochemistry demonstrated greater human T cell numbers in infected versus uninfected huNSG mice (p <0.05), and that T-bet+ human T cells clustered around the SACs, suggesting S. aureus-mediated activation and proliferation of human T cells in the infected bone. Collectively, these proof-of-concept studies underscore the utility of huNSG mice for studying an aggressive form of S. aureus osteomyelitis, which is more akin to that seen in humans. We have also established an experimental system to investigate the contribution of specific human T cells in controlling S. aureus infection and dissemination.